Implementation of Education Management In High Schools /Vocational Schools In North Sumatra - Yulita Triadiarti; La Ane; Erny Luxy D. Purba; Salsabila Irfan; Dandi Abdul Halim (Publikasi Indonesia, 2022)
This study conducted an analysis of the implementation of education management in High Schools / Vocational schools in North Sumatra. The implementation of the study was carried out related to the phenomenon that high schools / vocational schools still do not provide minimum standard technical services in accordance with the Regulation of the Minister of Education and Culture Number 32 of 2021 concerning Technical Standards for Minimal Education Services. The population in this study is all private high schools / vocational schools in North Sumatra. Sampling was carried out using Cluster Sampling with sampling mapping based on the number of regencies/cities in North Sumatra. The study was conducted qualitatively. The data is collected in a primary manner which is then analyzed and discussed through a Focus Group Discussion with the principal and teachers. The results of the analysis concluded that in general the implementation of secondary education management has been carried out well in high schools / vocational schools in North Sumatra. Based on the results of the descriptive qualitative analysis, it proves that some implementation of educational standards has gone very well. The implementation of education implementation that still faces several obstacles is the implementation of financing standards, procedures for meeting standards, implementation of standards for the number of educators and education personnel, implementation of quality standards for educators and education personnel, and implementation of student personal cost standards as measured by the fulfillment of basic student equipment.